The Impact of Stellar Rotations and Binaries on the Shape of Upper Main Sequence near Turnoff in Open Cluster NGC 6067 - Jayanand Maurya; Yu Zhang; Sebastian Kamann; Hubiao Niu; Yves Frémat; Kaixiang Lang; Y. C. Joshi; M. R. Samal; Peter De Cat; Ali Esamdin (The Astrophysical Journal)
We present the analysis of the extended main-sequence turnoff (eMSTO) in the open cluster NGC 6067. We derive the projected rotational velocity, v sin i , of the stars belonging to the eMSTO region of the main sequence (MS) utilizing Gaia-ESO spectra. Our results reveal a positive correlation between v sin i and the color of eMSTO stars, where fast-rotating stars predominantly occupy the red part of the MS while slow-rotating ones prefer a bluer side of the MS. The gravity-darkening effect might be a reason for this correlation. We find that most of the close binaries present in the eMSTO population would be slow-rotating due to the tidal-locking phenomenon. We identify four double-lined spectroscopic binaries (SB2) featuring slow-rotating companions, further supporting this tidal-locking hypothesis. However, the spatial distribution and the cumulative radial distribution indicate a higher concentration of red eMSTO stars in the cluster’s central region than their bluer counterparts. This suggests that tidal locking is less likely to be the cause of the observed spread in rotation rates among eMSTO stars. Instead, we propose that star–disk interactions during the pre-main-sequence phase might have played a crucial role in spreading the rotation rates of stars, leading to the eMSTO phenomenon in NGC 6067.